Case Report: The second valve drag technique for managing acute total obstruction of the right coronary artery during transcatheter aortic valve replacement - Song, Yanbin; Zhang, Xiaochun; Zhou, Daxin; Pan, Wenzhi (Frontiers in Cardiovascular Medicine, 2025)
IntroductionDespite technological advancements and new generation devices availability, transcatheter aortic valve replacement (TAVR) for bicuspid aortic valve (BAV) stenosis still presents unique technical challenges.Methods and resultsWe report an uncommon but critical complication of acute right coronary artery occlusion resulting from valve dislocation during TAVR. For the first time, we employed novel approach, namely second valve dragging, to address mispositioned self-expanding valve. This implementation of novel and successful interventional treatment led to the rapid relief of coronary obstruction.DiscussionThis innovative approach offers a promising avenue for further management of these patients in critical conditions.